1965
DOI: 10.3758/bf03343313
|View full text |Cite
|
Sign up to set email alerts
|

The development of water drinking on a dry-food free-reinforcement schedule

Abstract: Rats were given a food pellet every 60 sec., not contingent on operant responding. All rats developed over days a pattern of prolonged water drinKIng !allowing delivery of food pellets. One of the rats, whose operantlevel lever pressing was recorded concurrently with licking, developed a complex pattern of drinking and bar pressing which persisted even after a 5-sec. delay of reinforcement for bar presses was introduced. Problem Several investigators have reported unusual frequ€mcies and quantities of water dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
0
1

Year Published

1967
1967
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 6 publications
1
25
0
1
Order By: Relevance
“…Schedule induced polydipsia, originally described by Falk (1961aFalk ( , 1961b has been interpreted as due to adventitious reinforcement (Clark, 1962;Segal, 1965). stein (1964) found little supporting evidence for an adventitious reinforcement explanation and as an alternative suggested that rats have a tendency to drink after eating dry food.…”
mentioning
confidence: 99%
“…Schedule induced polydipsia, originally described by Falk (1961aFalk ( , 1961b has been interpreted as due to adventitious reinforcement (Clark, 1962;Segal, 1965). stein (1964) found little supporting evidence for an adventitious reinforcement explanation and as an alternative suggested that rats have a tendency to drink after eating dry food.…”
mentioning
confidence: 99%
“…Although the possibility cannot be ruled out that with more sessions eventually even these RI rats might have developed interim drinking, the lack of any systematie upward trends in either their drinking or licking makes this seem unlikely. EIsewhere it has been shown that schedule-induced drinking under VI 60-lSec and similar schedules generally is asymptotie by 10 to 15 sessions (e.g., King & Schaeffer, 1973;Sanger & Blackman, 1975;Segal, 1965).…”
mentioning
confidence: 99%
“…In particular, none of the pigeons in the present experiment, with the exception of S3 on the FI 50-sec schedule, increased their mean bout frequencies or durations across sessions within an experimental condition. Rats exposed to intermittent food presentations avidly increase both the frequencies and durations of their drinking bouts [20], although the mean water intake per bout eventually stabilizes and appears to be orally monitored and regulated [9,12]. The finding that polydipsia is reliably induced in rats, but not in pigeons, exposed to FI food reinforcement schedules seems to depend on the fact that rats, but not pigeons, increase their drinking frequencies and tend to drink after virtually every food presentation.…”
mentioning
confidence: 93%